Assessing Elite Athletes Using PROMIS Tools: The STEALTH Project (Student Athlete Health Assessment). Issue 7 (31st July 2020) - Challa, Shanthan; Holliday, Marissa; Bartolomei, Kenneth; Bartolomei, Jonathan
Objectives: Injuries are a major part of elite sports, and patient-reported outcomes tools (PROs) are becoming commonplace for the assessment of injury and treatment outcomes. The National Institutes of Health (NIH) Patient-Reported Outcomes Measurement Information System (PROMIS) is a validated set of assessment tools with increasing popularity. The PROMIS metrics utilize computerized adaptive testing (CAT) to capture health status measurements through individualized assessments, with minimal user burden, and without the loss of precision or content validity. The purpose of this study was to evaluate elite athletes using PROMIS scores and assess the impact of injury on those scores to gain insight into how participation and injury can impact the health of NCAA Division 1 athletes participating in a variety of sports. Methods: Over six months, athletes from 11 sports at a single Division 1 Athletics program were recruited to participate in longitudinal prospective data collection using four PROMIS CAT scales/domains: Pain Interference (PI), Physical Function (PF), Depression, and Ability to Participate in Social Roles and Activities (PSRA). Using REDCap (Research Electronic Data Capture), athletes completed an assessment that included the PROMIS tools before participation in their respective sport's season for the 2018-2019 academic year and following the completion of their season. Athletes suffering a season-ending injury were asked to complete the PROMIS survey within a week following the injury. De-identified data was analyzed using Student's T-test. PROMIS outcome measures were analyzed using linear mixed model regression. A p-value of < 0.05 was considered statistically significant. Results: A total of 592 surveys were collected, composed of 320 pre-season surveys, 241 post-season surveys, and 31 season altering injury surveys. PF, Depression, and PSRA scores were significantly different in athletes than in the general age-matched population (Fig 1). PI scores were similar to the normal population. The distribution of PI and PF scores were significantly different pre and post-season with a difference in means of 1.499 (p=0.030) and -2.019 (p=0.005), respectively. No significant difference was observed in the Depression and PSRA scores at the end of the season (Fig 1). A total of 31 significant injuries were reported. Injuries resulted in a significant change from pre-season to post-season scores amongst all participants (Fig 1). Conclusion: There were significantly worse pain interference and physical function scores post-season compared to preseason, suggesting that athletic participation alone may impact the athlete's overall function and condition. Season-altering injuries resulted in clinically significant differences in all four domains, PI, PF, Depression, and PSRA, suggesting that injuries greatly affect athletes not only physically, but mentally and socially as well. Statistically significant changes were seen in depression and social metrics after injury compared to the athlete's pre-season scores. Consideration should be given to index pre-season PROMIS scores for individual athletes to make follow-up scores athlete-specific, meaningful, and actionable. There is a clear need for additional investigation into the impact of specific sports and specific injuries, which would be valuable to trainers, coaches, and clinicians to inform treatment and return to sport protocols.